Pengaruh Motıvası Kerja Dan Kedısıplınan Terhadap Kınerja Guru Sekolah Dasar Negerı dı Kabupaten Lebak - Trio, Dine; Udin Syaefudin Sa'ud; Mubiar Agustin; Johar Permana (Elementary Teacher Education Program, Majalengka University, 2023)
The performance of a teacher includes his ability to carry out teaching tasks in schools and responsibilities towards students who are under his influence. There are several factors that influence teacher performance including those determined by work motivation and discipline factors. The purpose of this study was to describe the influence of work motivation and discipline on the performance of Lebak District Elementary School teachers. The method used in this research is descriptive verification. The data in this study were obtained through questionnaires which were distributed to 100 teachers and then analyzed using multiple regression analysis. The results showed that partially work motivation contributed 67.1% to teacher performance and discipline contributed 59.8% to teacher performance variables. While simultaneously, work motivation and discipline contribute 74.2% to teacher performance. So it can be concluded that, 1) work motivation encourages improving the performance of Lebak Regency SDN teachers; 2) Discipline encourages improving the work performance of Lebak Regency SDN teachers; 3) Work motivation and discipline simultaneously affect the performance of Lebak Regency SDN teachers.